ANTIBIOTIC USE AT PRIMARY HEALTHCARE CENTERS IN SURABAYA: A SURVEILLANCE STUDY - Herawati, Fauna; Hartono, Ivan D.; Pranajaya, Dicky; Narindra, I. Putu Hendryx (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Antibiotics are considered to be overprescribed in primary health care centers. This study aimed to investigate the defined daily dose (DDD) of antibiotics per 1000 patients visit in a year in primary health care centers, the prevalence of upper respiratory infections (URI) and diarrhea, the percentage of antibiotic prescription for URI and diarrhea in Surabaya. Methods: A surveillance study of antibiotic use was done from the reports and use of drug demand sheet, which called laporan pemakaian dan lembar permintaan obat (LPLPO), outpatient medication card, and health care information and management system of primary health care center, which called sistem informasi manajemen manajemen puskesmas (SIMPUS) in Surabaya. DDD/1000 patients were calculated for describing the antibiotics usage level in each primary health care centers. Three primary health care centers selected based on its antibiotic use or its population density to recognize its antibiotic prescribing percentage for non-pneumonia respiratory tract infection and nonspecific diarrhea. Results: The DDD antibiotic systemic per 1000 patients visit primary health care centers in Surabaya is relatively low. The results found higher prevalence URI does not correlate to the frequent antibiotic prescribed. The prevalence of URI at one primary healthcare center (25% cases) was less than at the other (44%), but the percentage of antibiotic prescription and the total antibiotic usage were higher (73%; 1006 DDD/1000 patients vs. 21%; 675 DDD/1000 patients). The prevalence of diarrhea at primary health care center 2 (2,84%) was less than at primary health care center 1 (4,95%), but the percentage antibiotic prescription and the total antibiotic usage were higher (43%; 1006 DDD/1000 patients vs 18%; 675 DDD/1000 patients). Conclusion: The antibiotic usage at primary healthcare centers in Surabaya was shown to vary widely. Eighty-seven percent (55/63) primary health care centers antibiotic usage was less than 4 DDD/1000 patients day, only two primary health care centers antibiotic usage 6 DDD/1000 patients day. Further research to investigate antibiotic usage and the differences in usage between primary health care centers in treating URI is required.